Laser Welding 2010
DOI: 10.5772/9857
|View full text |Cite
|
Sign up to set email alerts
|

Low Speed Laser Welding of Aluminium Alloys Using Single-Mode Fiber Lasers

Abstract: Background and Reviews Aluminium AlloysAluminium alloys can be separated into two major categories: Non heat-treatable and heattreatable. The initial strength of non heat-treatable alloys depends primarily upon the hardening effect of alloying elements such as silicon, iron, manganese and magnesium. The non heat-treatable alloys are mainly found in 1xxx, 3xxx, 4xxx and 5xxx series. Additional strength is usually achieved by solid-solution strengthening or strain hardening. The initial strength of heat-treatabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Wu et al [51] found that the surface tension of the molten metal and the recoil pressure caused by evaporation were responsible for the spatter formation. The oxide layer formation on the surface of the molten metal is associated with the high affinity of Al to O 2 , which can prevent the escape of bubbles from the weld metal [52,53].…”
Section: Appearance Of Laser Weldsmentioning
confidence: 99%
“…Wu et al [51] found that the surface tension of the molten metal and the recoil pressure caused by evaporation were responsible for the spatter formation. The oxide layer formation on the surface of the molten metal is associated with the high affinity of Al to O 2 , which can prevent the escape of bubbles from the weld metal [52,53].…”
Section: Appearance Of Laser Weldsmentioning
confidence: 99%
“…Also, there is some evidence that the bubble velocity is suppressed during turbulent flow [24]. The solidification rate during laser welding of aluminum has been suggested to be up to 10 5°C s −1 or higher [25,26]. Under this condition, the weld metal solidifies more rapidly than the possible rise velocity of the gas bubbles formed during keyhole collapse, resulting in severe porosity in the weld metal.…”
Section: Resultsmentioning
confidence: 99%
“…Molten pool instabilities in the root area may cause gas bubbles. The high affinity of titanium to oxygen can give rise to the formation of an oxide layer on the melt very quickly, which impedes gas bubbles escape [34,35]. In deep penetration welding, the weld depth is increased, but due to the formation of the gaseous keyhole, the risk of process defects is increased.…”
Section: Introductionmentioning
confidence: 99%